Do ato de aprender ao ato de ensinar: a história de vida e os diferentes saberes na construção de minha identidade profissional docente - QUARESMA, Maria do Carmo Maués (2024)
This memorial comes to my memories about the act of learning the act of teaching: landmarks reminiscent of the story of my life and different knowledge to build my teacher professional identity. Intends to present the theoretical ideas embricaram up to my family, academic and vocational training. Highlighting the origin of memories about my life, and my passage through basic and higher education, as well as in working with in-service training. So, I found methodological theoretical foundation in qualitative descriptive approach using the technique of preparing a memorial. My overall goal is to understand how landmarks reminiscent of the story of my life and different knowledge influenced my act of learning and building my teacher professional identity, and present memories of significant events of Family Education and Formal Education that led me to understand how I learned; Highlight the different knowledges which amounted to build my teacher professional identity; Analyze the contributions of the different way of learning to like me, a literacy teacher education today. I concluded that teacher identity is produced through various learning, knowledge from themselves and others that there is a close and dynamic relationship between history and life that interferes with the way we learn and teach and that there are always possibilities of change on a personal level professional especially when we recognize the implicit and explicit contributions arising from many different knowledge.